Women’s Sex Representation in Comic Book (Proceedings of the International Conference on Future of Women, 2020)
The representation of women has always been different in comics from past to present.Some women have been shown in the comics, in the role of being saved by a male superhero, or in asexy female image with pornographic elements. The scarcity of female illustrators and writers, beingmale among publishers consists of the necessary information for the research of comics among thegender studies. Just as there are gender and objectification elements in real life, there are also theseapproaches to the female body in comics. Towards the 21st century, together with the movements offeminism, both the technological conditions and the digitization of the comics have made women'srepresentation a little more free. For this reason, the methodology of the research has beendetermined as Fourth Wave Feminism. Now, they can explain the female lesbian culture and sexualpolicies independently of society in the comics of Alison Bechdel's Fun Home and a series of imagesthat depict Belden Sezen's A Snapshot. The handling of such female characters in comic books andgraphic novels firstly enables the students to make accurate determinations while breaking theprejudice of the society, and then when determining the orientation of the young generation, and thatwomen can live their identity freely as an individual. Based on all these information and results, inthis research, the representation of women in comics will be explained through a historicalevaluation and then criticized in terms of gender.
Keywords: comics; women; gender representation; objectification